2016
DOI: 10.1016/j.jand.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Adult Intake of Minimally Processed Fruits and Vegetables: Associations with Cardiometabolic Disease Risk Factors

Abstract: Background The U.S. Department of Agriculture launchedChooseMyPlate.gov nutrition recommendations designed to encourage increased fruit and vegetable intake in part as a strategy for improving weight control through the consumption of high satiation foods. Objective The purpose of this cross-sectional study was to assess the relationship between adults’ reported daily intake of fruits and non-starchy vegetables (i.e., those thought to have the lowest energy density) expressed as a proportion of their total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Cavallo et al found that lower fruit and vegetable intake, compared with that of other foods consumed, were associated with lower fasting insulin levels. 28 A meta-analysis of 12 studies concerning the impact of fruit juice consumption (about 50-500 mL per day) on fasting glucose and insulin level and HOMA-IR values did not show any significant relation between this habit and fasting glucose and insulin levels. Only 3 studies confirmed a significant correlation between juice consumption and increased HOMA-IR values.…”
Section: The Relationship Between Consumption Of High-fiber Products mentioning
confidence: 92%
“…Cavallo et al found that lower fruit and vegetable intake, compared with that of other foods consumed, were associated with lower fasting insulin levels. 28 A meta-analysis of 12 studies concerning the impact of fruit juice consumption (about 50-500 mL per day) on fasting glucose and insulin level and HOMA-IR values did not show any significant relation between this habit and fasting glucose and insulin levels. Only 3 studies confirmed a significant correlation between juice consumption and increased HOMA-IR values.…”
Section: The Relationship Between Consumption Of High-fiber Products mentioning
confidence: 92%
“…Studies have shown that plants, particularly colorful fruit or vegetable-bearing plants, contain polyphenolic compounds that have potent antioxidant and antiinflammatory activities, 88 and increased fruit and vegetable intake has been associated with reduced fasting insulin levels. 89 Evidence is accumulating that consumption of these polyphenol-rich foods, particularly berry fruit, may be a strategy to forestall or even reverse age-related neuronal deficits resulting from neuroinflammation. 90 Recently this evidence has been extended to doubleblind, placebo-controlled, randomized human intervention studies that have demonstrated that the consumption of flavonoid/ polyphenols is associated with benefits to cognitive function.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
“…62,63 Nutritional Intervention. In the face of clear recommendations from the U.S. Department of Agriculture, U.S. Department of Health and Human Services, and National Cancer Institute supporting adequate daily intake of fruits and vegetables to prevent many chronic diseases, the majority of Americans do not meet their nutrient requirements 64,65 (Table 1). Also, adequate fiber intake, essential for production of SCFAs and protective to the intestinal colonocytes and beneficial gut bacteria, is lacking in the USA.…”
Section: Lifestyle Interventions For Neuropathymentioning
confidence: 99%